Uganda's experience with aid - Kasekende, Louis (Oxford academic, 1999)
This paper presents Uganda's experience with aid flows over the period 1970-96. It discusses the compilation of aid data and also reviews the chronological developments in aid flows to Uganda. Over this period, the sectoral distribution and type of aid is largely dictated by the government's economic programmes in place. The period 1962-71 largely reflects government borrowing for on-lending to agriculture and industry whereas the period 1979-85 shows a wider range of sector-specific programmes driven by the need to reconstruct and rehabilitate the economy. Although the need to reconstruct and rehabilitate the economy continued, support for policy reform began to take up an increasing proportion of aid over the period 1987-96. We also analyse the impact of aid on some major macroeconomic variables and find that investment and real exchange rate developments have been largely driven by official development aid flows. Although we find a similar relationship between aid and improved policy environment, the findings show that in the latter part, i.e., 1992-6, the continued policy reform was driven more by ownership of the programme than by aid. Indeed, in this latter period, the aid/GDP ratios declined. The major lesson drawn from this study is that ownership of a reform programme is more critical for its success, hence our conclusion that aid should be used for financing rather than buying reforms.
Keywords: Aid; Uganda